2011
DOI: 10.1111/j.1751-2980.2011.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T‐lymphocyte antigen 4 gene +49A/G polymorphism significantly associated with susceptibility to primary biliary cirrhosis: A meta‐analysis

Abstract: OBJECTIVE:To evaluate comprehensively the association of cytotoxic T-lymphocyte antigen 4 (CTLA-4) +49A/G polymorphism with susceptibility to primary biliary cirrhosis (PBC). METHODS:PubMed was used to search for the relevant published articles. The risk of PBC association with the CTLA-4 +49A/G polymorphism was estimated for each study in a random-effects model. Odds ratio (OR) and 95% confidence interval (CI) were estimated for each study. Risks to PBC were estimated by stratified analysis in patients with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
2
5
0
Order By: Relevance
“…For patients in cases, the frequencies of allele and genotype in rs231775 and rs231725 were increased more significantly than those in controls. As to allele, the results of rs231775 were similar to the results of five published meta-analyses by Eskandari-Nasab et al [39], Huang et al [23], Miyake et al [24], Li et al [25], and Chen et al [14]. Li and Miyake indicated that the G allele might be connected with PBC as a risk factor.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For patients in cases, the frequencies of allele and genotype in rs231775 and rs231725 were increased more significantly than those in controls. As to allele, the results of rs231775 were similar to the results of five published meta-analyses by Eskandari-Nasab et al [39], Huang et al [23], Miyake et al [24], Li et al [25], and Chen et al [14]. Li and Miyake indicated that the G allele might be connected with PBC as a risk factor.…”
Section: Discussionsupporting
confidence: 84%
“…Recent study showed that PBC was significantly associated with some concrete gene polymorphisms [14]. Since PBC displays characteristics of autoimmunity, more and more studies concentrated in associations between genetic polymorphism and variations of autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, they are reminiscent of similar observations reported by a number of research groups, including our own, in other autoimmune diseases (both systemic and organ-specific) [26][31], [33], [34], and in other immunological or haematological disorders, such as IgE-mediated reaction to hymenoptera venom [35], or acute lymphoblastic leukemia (ALL) in paediatric patients [36]. In some of these conditions, sCTLA-4 concentrations appeared to be somehow correlated with disease activity or outcome (e.g.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, there is still a debate about the spliced/shaded nature of the soluble variant of CTLA-4 [27], [34], [36], [39]. Moreover, the relationship between CTLA-4 polymorphism(s) described associated with autoimmune diseases (including PBC) [33] and the ability to produce the spliced soluble form of the molecule has been not yet elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported that the PTPN22 polymorphism C1858T is associated with GD, it has not been observed to influence the risk of PBC in previous studies [28,29]. However, some studies have suggested that polymorphism in exon 1 of the CTLA-4 gene at position 49 (+49A/G, rs231775) may influence the risk of GD [27,30] and also the risk of PBC [31][32][33]. Therefore, genetic factors such as CTLA-4 may be a candidate for a susceptibility locus driving concomitant cases of PBC and GD, although further investigations to identify common genetic factors in both PBC and GD are warranted.…”
Section: Genetic Factors Associated With Both Pbc and Gdmentioning
confidence: 97%